Targeting Histone Deacetylases for the Treatment of Huntington's Disease - Gray, Steven G. (CNS Neurosci Ther, 2010)
Huntington's disease is a debilitating neurodegenerative condition with significant burdens on both patient and healthcare costs. Despite the identification of the causative element, an expanded toxic polyglutamine tract in the mutant Huntingtin protein, treatment options for patients with this disease remain limited. In the following review I assess the current evidence suggesting that a family of important regulatory proteins known as histone deacetylases may be an important therapeutic target in the treatment of this disease.